Following better things: Grammar schools, religion and English rock music in the early 1970s. (4th October 2019) - Mutch, Alistair
Abstract : Examination of the secondary schooling of successful English and Welsh rock musicians of the early 1970s indicates the significance of the grammar school. Nearly half of 'progressive' rock musicians had a grammar school education, but even among 'classic' rock musicians, grammar school-educated players were over-represented compared to the figures for the population as a whole. The impact of a grammar school education is then explored through an examination of the work of Ian Anderson and Jethro Tull, indicating the Church of England ethos that dominated grammar schools of the period and which continued to have an influence on the form of progressive rock as a genre. Secondary education has been rather neglected as an important factor conditioning the nature of music but might help to explain band dynamics and the development of particular genres.